Hydrophilic Tetraphenylethene-Based Tetracationic Cyclophanes: NADPH Recognition and Cell Imaging With Fluorescent Switch - Wu, Dan; Zhang, Zhankui; Yu, Xinyang; Bai, Bing; Qi, Shaolong (Frontiers in Chemistry, 2021)
A hydrophilic TPE-based tetracationic cyclophane TPE-cyc was synthesized, which could capture intracellular Nicotinamide adenine dinucleotide phosphate and fuel the antioxidative ability of tumor cells to detoxify reactive oxygen species (ROS). Meanwhile, upon the reduction by cellular GSH, TPE-cyc could light up tumor cells, acting as a GSH-responsive fluorescent switch to image cells with high resolution.